Osmosis Drives Explosions and Methane Release in Siberian Permafrost - Morgado, Ana M. O.; Rocha, Luis A. M.; Cartwright, Julyan H. E.; Cardoso, Silvana S. S. (Geophysical Research Letters, 2024)
Mysterious craters, with anomalously high concentrations of methane, have formed in the Yamal and Taymyr peninsulas of Siberia since 2014. While thawing permafrost owing to climate warming promotes methane releases, it is unknown how such release might be associated with explosion and crater formation. A significant volume of surface ice-melt water can migrate downward driven by osmotic pressure associated with a cryopeg, a lens of salty water below. Overpressure reached at depth may lead to the cracking of the soil and subsequent decomposition of methane hydrates, with implications for the climate.